Effects of the 2008 flood on economic performance and food security in Yemen: A simulation analysis - Breisinger, Clemens; Ecker, Olivier; Thiele, Rainer; Wiebelt, Manfred (Wiley, 2016)
Extreme weather events such as floods and droughts can have devastating consequences for individual well being and economic development, in particular in poor societies with limited availability of coping mechanisms. Combining a dynamic computable general equilibrium model of the Yemeni economy with a household‐level calorie consumption simulation model, this paper assesses the economy‐wide, agricultural and food security effects of the 2008 tropical storm and flash flood that hit the Hadramout and Al‐Mahrah governorates. The estimation results suggest that agricultural value added, farm household incomes and rural food security deteriorated long term in the flood‐affected areas. Due to economic spillover effects, significant income losses and increases in food insecurity also occurred in areas that were unaffected by flooding. This finding suggests that while most relief efforts are typically concentrated in directly affected areas, future efforts should also consider surrounding areas and indirectly affected people.